The Relationship of Family-Based Self-Management Education Programs with Quality of Life of Patients with Type II Diabetes Mellitus at Limboto Health Center - Rahmat Natuwa; Nuridana Djamaluddin; Muh. Syukriani Yusu (Universitas Muhammadiyah Palu, 2026)
Type II diabetes mellitus is a chronic disease that requires long-term management because it can cause various complications and have an impact on reducing the quality of life of sufferers. Diabetes control does not only depend on medical therapy, but also requires the patient's ability to self-manage. One of the efforts that can be made to improve these abilities is the family-based Self-Management Education program which aims to improve knowledge, skills, and family support in the treatment of people with diabetes mellitus. This study aims to determine the relationship between family-based Self Management Education programs and the quality of life of people with type II diabetes mellitus at Limboto Health Center. This study uses a quantitative method with a cross sectional design. The research was carried out at the Limboto Health Center from December to January. The population in this study amounted to 184 patients with type II DM with a sample of 65 respondents selected using purposive sampling techniques. Data collection was carried out using questionnaires to measure the level of self-management and quality of life of respondents. Data analysis was carried out univariate and bivariate to determine the relationship between the two research variables. The results showed that some respondents had a poor quality of life category as many as 31 people (47.7%), while respondents with good self-management amounted to 28 people (43.1%). The results of the analysis showed a relationship between the family-based Self Management Education program and the quality of life of people with type II diabetes mellitus. The conclusion of this study is that the family-based Self Management Education program has a relationship with the quality of life of people with type II diabetes mellitus. Therefore, the implementation of educational programs involving families is important to improve the self-management skills and quality of life of people with diabetes mellitus.